(untitled) (Oxford, UK, 1987)
This book improves the speaking ability of elementary students of English. The activities are task-based and provide practice in exchanging opinions, sharing experiences, passing on information, developing conversations and telling short stories.
Keywords: English language,English language; Speaking,Text books for foreign students